Employee Perception on Compensation Management Practices: A Study on Apollo Glengeales Hospitals, Kolkata. (Global Business Management Review (GBMR), 2022)
Retaining talents in the healthcare sector had been an issue of challenge for HR practitioners. The healthcare sector in India oflate had seen tremendous growth with the influx of more patients seeking quality medical and healthcare services. In this context the number of hospitals had been far lesser in contrast with the growing needs of healthcare and medical facilities in the nation. Employees, medical professionals and technicians had experienced a challenging scenario to cope up with the stress of providing quality services with limited resources and infrastructure. On the HR perspective, it had become far difficult for hospitals to retain highly qualified professionals and employees, with more and more new hospitals growing in and around India. One of the major retention factors have obviously been “Compensation and Reward” related issues. Organizations with highly competitive compensation and reward packages have been reported to allure professionals for leaving their present job assignments. Taking this perspective into consideration, an attempt has been made in this study to have an insight on what healthcare professionals perceived regarding the compensation management practices with reference to those working in Apollo Glengeales Hospitals, Kolkata.